Entrepreneurship as a Catalyst for Rural Tourism Development - Sharif, Norhafiza Md; Lonik, Ku Azam Tuan (EDP Sciences, 2014)
The tourism industry is seen as capable of being an agent of change in the landscape of economic, social and environment of a tourist destination. Tourism activity has also generated employment and entrepreneurship opportunities to the local community as well as using available resources as tourist attractions. The tourism sector has the potential to be a catalyst for the development of entrepreneurship and small business performance. Through the development of tourism, the rural community has the opportunity to offer services or sell products to the both local and foreign tourists. To fulfill this purpose, local community participation in entrepreneurship is very important in order to develope the economic potential and to determine the direction of a development in rural areas. In the context of entrepreneurship, local participation is important not only as an entrepreneur and labor in this sector as well as complementary sectors of the others, but they can serve to encourage the involvement of other residents to join together to develop this entrepreneurial. This article aims to discuss the extent of entrepreneurship as a catalyst to the development of tourism in rural areas. Through active participation among community members, rural entrepreneurship will hopefully move towards prosperity and success of rural development.